2020
DOI: 10.1177/0363546520930713
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Malalignment Is Associated With Patellofemoral Lesions and Cartilage Relaxation Times After Hamstring Autograft Anterior Cruciate Ligament Reconstruction

Abstract: Background: There is growing evidence suggesting a link between patellofemoral joint (PFJ) osteoarthritis in anterior cruciate ligament (ACL)–reconstructed knees and altered joint alignment. Purpose: To determine whether patellar alignment differs between participants with and without ACL reconstruction (ACLR) and to identify possible associations between patellar alignment and PFJ osteoarthritis features over 3 years. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 37 participants with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…5 Although Capin et al 5 found associations between slower walking speed at 3 months after ACLR and higher trochlear cartilage T2 values at 6 months, the absence of T2 associations with other gait metrics in that work likely reflects that gait was assessed just 3 months after surgery when new loading patterns may not have been fully established. Other works compared static, unloaded patellar alignment 32 or tibial rotation 31 (derived from MRI scans) with patellofemoral cartilage T2 and T1ρ times. Liao et al 32 found that excessive patellar lateral displacement 6 months after reconstruction was associated with elevated lateral patellofemoral compartment T1ρ and T2 values 3 years later.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Although Capin et al 5 found associations between slower walking speed at 3 months after ACLR and higher trochlear cartilage T2 values at 6 months, the absence of T2 associations with other gait metrics in that work likely reflects that gait was assessed just 3 months after surgery when new loading patterns may not have been fully established. Other works compared static, unloaded patellar alignment 32 or tibial rotation 31 (derived from MRI scans) with patellofemoral cartilage T2 and T1ρ times. Liao et al 32 found that excessive patellar lateral displacement 6 months after reconstruction was associated with elevated lateral patellofemoral compartment T1ρ and T2 values 3 years later.…”
Section: Discussionmentioning
confidence: 99%
“…Other works compared static, unloaded patellar alignment 32 or tibial rotation 31 (derived from MRI scans) with patellofemoral cartilage T2 and T1ρ times. Liao et al 32 found that excessive patellar lateral displacement 6 months after reconstruction was associated with elevated lateral patellofemoral compartment T1ρ and T2 values 3 years later. However, Li et al 31 found only “scattered clusters of voxels” demonstrating elevations of these MRI metrics in cases of ACLR with greater external tibial rotation versus those with more normal rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported excessive patellar lateral displacement and lateral tilt at 6 months after ACLR in either static or dynamic tasks. 16,17,33 One study reported increased patellar lateral rotation (valgus rotation) during a static lunge, 33 whereas others reported decreased patellar lateral rotation. 16,17 From a biomechanical standpoint, altered patellar kinematics may lead to decreased PFJ contact area and elevated contact forces, 28 suggesting detrimental effects on the articular cartilage of the patella and trochlea.…”
mentioning
confidence: 99%
“…16,17,33 One study reported increased patellar lateral rotation (valgus rotation) during a static lunge, 33 whereas others reported decreased patellar lateral rotation. 16,17 From a biomechanical standpoint, altered patellar kinematics may lead to decreased PFJ contact area and elevated contact forces, 28 suggesting detrimental effects on the articular cartilage of the patella and trochlea. Indeed, studies have demonstrated associations between patellar malalignment and worsening of PFJ cartilage lesions as well as changes in cartilage composition, 16,18,19 both of which are features of early OA degeneration.…”
mentioning
confidence: 99%